2023
DOI: 10.1038/s41467-023-38501-w
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D3 degrades mitochondrial DNA to regulate nucleotide signaling and APP metabolism

Zoë P. Van Acker,
Anika Perdok,
Ruben Hellemans
et al.

Abstract: Phospholipase D3 (PLD3) polymorphisms are linked to late-onset Alzheimer’s disease (LOAD). Being a lysosomal 5’-3’ exonuclease, its neuronal substrates remained unknown as well as how a defective lysosomal nucleotide catabolism connects to AD-proteinopathy. We identified mitochondrial DNA (mtDNA) as a major physiological substrate and show its manifest build-up in lysosomes of PLD3-defective cells. mtDNA accretion creates a degradative (proteolytic) bottleneck that presents at the ultrastructural level as a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…L308P of hPLD3 has been genetically associated with SCA, and its 5¢-exonuclease activity was found to be impaired [47,48]. In a recent paper, it was suggested that PLD3 can degrade mitochondrial DNA to block cGAS/STING activation and thereby possibly prevent neurodegenerative diseases [49,50]. For PLD4, several disease-associated mutants have been reported in the Genome Aggregation Database (gnomAD) [51] (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…L308P of hPLD3 has been genetically associated with SCA, and its 5¢-exonuclease activity was found to be impaired [47,48]. In a recent paper, it was suggested that PLD3 can degrade mitochondrial DNA to block cGAS/STING activation and thereby possibly prevent neurodegenerative diseases [49,50]. For PLD4, several disease-associated mutants have been reported in the Genome Aggregation Database (gnomAD) [51] (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that dcNUMTs are transcribed and may have a function on the RNA level, or that the DNA itself has some regulatory function as observed for mitochondrial DNA (Acker et al 2023) or creates novel exons (Noutsos et al 2007). For example, the transcription of non-coding genomic DNA is very common (Gao et al 2020) and active retroviruses (Bolisetty et al 2012) may could lead to expression of NUMTs as well.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, altering the activity of phospholipase D3, a risk gene of late-onset AD, significantly impacted APP processing and cholesterol metabolism. 39…”
Section: Cholesterol Homeostasis and Apoe In Admentioning
confidence: 99%